Teknik Penyinaran Radioterapi Tiga Dimensi (3D) pada Pasien dengan Kasus Kanker Sarkoma Sinovial di Unit Radioterapi Instalasi Radiologi RSUP dr. Kariadi Semarang - Rizky Dika Hermawan; Siti Masrochah; Fatimah Fatimah (Jurnal Imejing Diagnostik (JImeD), 2021)
Background: Synovial sarcoma is a neoplasm that is clinically, morphologically, and genetically distinct. This spindle cell tumor shows epithelial differentiation that is not constant. Radiotherapy is one of the modes of treatment for synovial sarcoma cancer by using ionizing rays to kill or eliminate (eradicate) all cancer cells in the tissue. The goal of radiotherapy (radiation therapy) is to provide the required number of radiation doses precisely to the radiation target area without damaging the surrounding healthy tissue.Methods: The type of research used is an observational approach. With the patient object the remaining palmar synovial sarcoma. Data collection was carried out by direct observation of the patient. Data analysis was carried out by collecting data and documents, then drawing conclusions.Results: 3D irradiation technique in patients with synovial sarcoma cases at Dr. Kariadi Semarang is the administration of patient registration and doctor's examination with a plan of administering a total dose of 40 Gy with fractionation of 2 Gy per day and superficial brachytherapy or 30 gy electron. Making prints and checking the ct scan in the area of the hand then calculating the doctor and calculating tps. Verification of the ap field and then irradiating at an angle of PA (180º), AP (0º)Conclusion: 3D irradiation technique in patients with synovial sarcoma cases at Dr. Kariadi Semarang is patient administration, radiation planning, making molding and ct scan, contouring and tps calculations then doing field leverage and irradiation.